Digital visual literacy the librarian's quick guide - Fox, Nicole M. (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"This book is designed to be a quick, informative guide to visual literacy instruction in any classroom (higher education), not just the art or design classroom. In order to connect visual literacy instruction to the digital space it now occupies, this book also features several workshops and instruction sessions that use digital humanities tools. Each chapter discusses a different facet of visual literacy through a digital lens"--Provided by publisher.